Age-based life-history traits of two filefish from the Solomon Islands: the honeycomb (Cantherhines pardalis) and the broom (Amanses scopas) filefishes - Visconti, Valerio; Woodgate, Ian; Trip, Elizabeth D. L.; Sabetian, Armagan (Frontiers in Marine Science, 2025)
This study investigates the age-based life-history traits of two filefish species from the Solomon Islands, the Honeycomb filefish (Cantherhines pardalis) and the Broom filefish (Amanses scopas). The research aims to fill a significant gap in our understanding of tropical monacanthid demography by providing an age-based life-history assessment for these species. A total of 201 C. pardalis and 60 A. scopas were collected from the reefs offshore Vavanga Village, Solomon Islands, between January 2016 and February 2017. Age determination was based on thin transverse sagittal otolith sections, revealing that C. pardalis reaches a maximum age of 9 years (n=140, CV=6.7, APE=8.12), while A. scopas of 12 years (n=42, CV=2.5, APE=20.3). The study found marked differences in life-history strategies between the two species, with C. pardalis exhibiting rapid early growth and early maturation within its first year, whereas A. scopas grows more slowly and reaches a larger asymptotic size later in life. Sex-specific patterns in growth and length-weight relationships were observed, indicating differential energy allocation strategies. Mortality estimates align with expectations for small-bodied reef fishes subjected to natural predation and artisanal harvesting. The findings highlight divergent growth and reproductive strategies within a single family in the same reef system, underscoring the ecological plasticity of monacanthids.